Meta Analysis of the Outcomes in Doing Active Surveillance and Surgical Approach for Micropapillary Thyroid Carcinoma - Aryanti, Citra; Sudarsa, I Wayan; Tusta Adiputra, Putu Anda (Asian Pacific Journal of Environment and Cancer, 2022)
Introduction: Micropapillary thyroid carcinoma was emerging as an epidemic disease worldwide. Due to its unaggressiveness and slow-growing feature, either doing active surveillance or surgical approach were controversial for its management. This meta analysis aimed to determine the pooled proportion outcomes of doing active surveillance and surgery in micropapillary thyroid carcinoma. Methods: This meta analysis of the results in doing active surveillance and surgical approach for micropapillary thyroid carcinoma, designed followed the PRISMA guidelines. Relevant studies were obtained from Medline (2008-2018) and SCOPUS (2008-2018) in the last 20 years. The scope of data collection is about the author, year of study, and number of subjects. The parameter of this study was pooled proportion. Data were analyzed by MedCalc 13.5 and the significance limit was 0.05. Results: The pooled proportion of cases of surgery conversion, increasing tumor size more than 3 cm, and the presence of lymph node metastases during active surveillance of micropapillary thyroid carcinoma were 14.996; 6.125%; and 4.988%, respectively. The pooled proportion of cases of recurrence and lymph node metastases after surgery of micropapillary thyroid carcinoma were 3.539% and 14.071%, respectively. Discussion: In this study, it was showed that result was favorable in doing active surveillance. The rate of lymph node metastases were comparable in non and interventional group. However, this approach should be considered cases by cases. Many individual factors like age, gender, and comorbidities should be considered. Conclusion: Active surveillance was a safe and considered approach for micropapillary thyroid carcinoma. However, some risk factor should be considered for surveillance exclusion.